Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
3x2+12x=0
<=> 3x ( x + 4 ) = 0
<=> 3x = 0
và x+4 = 0
<=> x = 0
và x = -4
Vậy x = 0 và x = -4
3x2+12x=0
<=> 3x ( x + 4 ) = 0
<=> 3x = 0
và x+4 = 0
<=> x = 0
và x = -4
Vậy x = 0 và x = -4
b) 5x.(-x)2 + 1 = 6
=> 5.x.x2 = 6 - 1
=> 5.x3 = 5
=> x3 = 5:5
=> x3 = 1
=> x = 1
a) 3x2 + 12x = 0
=> 3x(x + 4) = 0
=> x(x + 4) = 0
=> x = 0 hoặc x + 4 = 0
+) x = 0
+) x + 4 = 0 => x = -4
Vậy: x \(\in\){0;-4}
a, 3x2 +12x=0
3x(x+4)=0
=> 3x=0 hoặc x+4=0
=> x=0 hoặc x= -4
Vậy x=0; x= -4
b, 4x3 = 4x
4x3- 4x=0
4x(x2- 1) =0
4x(x-1)(x+1)=0
=> 4x=0 hoặc x-1=0 hoặc x+1=0
=> x=0 hoặc x=1 hoặc x=-1
Vậy x=0; x=1;x=-1
c, ( x-1)(x+1)+2=0
x2- 1+2=0
x2+1=0
x2 = -1
=> x vô nghiệm
1) (3x-1)(-1/2x+5)=0
TH1: 3x-1=0
3x = 1
x = 1/3
TH2: -1/2x+5=0
-1/2x =-5
x = 10
2) (3/4-x)^3=-8
(3/4-x)^3=(-2)^3
=> 3/4-x=-2
x=3/4+2
x= 11/4
3) |2x-1|=-4^2
|2x-1|=16
=> 2x-1=-16 hoặc 2x-1=16
TH1: 2x-1=-16
2x =-15
x = -15/2
TH2: 2x-1=16
2x =17
x = 17/2
3x2.12x=0
=>3x2=0 hc 12x=0
TH1:3x2=0
=>x=0
TH2:12x=0
=>x=0
Vậy x=0
Tick nha !!!
\(3x^2+12x=0\)
=>\(3\left(x^2+4x\right)=0\)
=>\(x^2+4x=0\)
=>\(x\left(x+4\right)=0\)
=>\(\left[{}\begin{matrix}x=0\\x+4=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=0\\x=-4\end{matrix}\right.\)
\(3x^2+12x=0\)
\(3x.\left(x-4\right)=0\)
\(3x=0\) hoặc \(x-4=0\)
\(\Rightarrow x=0\) hoặc \(x=4\)